Mensur Şehname Tercümesi - Şahin, Sadettin (My University, 2000)
OF THESIS The book is registered under fixture number 6131 at the Central Library of Istanbul University. It is composed of 3 volumes with total pages of 1778. Also miniatures have taken place in the book with each page designed 25 lines. The length of the first volume on which work is being carried on, is 39 cm, width is 24.5 cm and thickness is based 7.5 cm. The work was completed on 1187 (date based on Hegira) or 1773 (date based on birth of Christ/ Christian era). It is not a translation word by word. The reason to prepare this thesis is to recognise the translation of ?EHNAME in prose. The thesis is composed of three sections which are the introduction, the text and the dictionary. The introduction section gives information about Firdevsi, ?ehname, ?ehname translations and hand prints/ paints on which work is carried on. The text shows the pages and line numbers and designed according to punctuation marks used up to date and paragraps have been created at the necessary parts. This way, it has been aimed to get benefit of the work more easily. The meanings of the Persian (Farsi) verses and arabian expressions have been clarified in meaning in footnotes. Furthermore, the parts regarded as heading have been identified in larger letters with darker characters. The dictionary is based on alphabetic and root principles. The wording accepted as the beginning (main) item has down below the intermediary item, expression and composed wording related to that word. The items identified as second, third factors of the main or intermediary items have been referred with marking (Æ).
Keywords: Edebiyat; İran edebiyatı; İran Edebiyatı_Şehname